School‐Level Factors Associated with Sun Protection Practices in California Elementary Schools. (6th March 2020) - Reynolds, Kim D.; Buller, David B.; Berteletti, Julia; Massie, Kim; Ashley, Jeff; Buller, Mary K.; Meenan, Richard T.; Liu, Xia
ABSTRACT: BACKGROUND: This study examined implementation of district sun safety policy in schools and tested correlates of implementation in California public school districts. METHODS: Principals (N = 118) and teachers (N = 113) in California public elementary schools (N = 118) were recruited and completed a survey on sun protection policies and practices. The sample contained schools whose districts subscribed to the California School Boards Association and adopted Board Policy 5141.7 for sun safety. Principals and teachers reported on implementation of 10 school practices related to BP 5141.7 indicating which practices were implemented in the school. RESULTS: Years in public education (Exponentiated Score (ES) = 0.51, p < .001), years worked in the current district (ES = 0.49, p < .001), perception that parents should take action to protect children from the sun (ES = 0.43, p < .01), and personal skin phenotype (Low Risk ES = 0.55; High Risk ES = 0.09, p < .05) were associated with number of practices implemented in the school using multiple Poisson regression. CONCLUSIONS: Policy implementation is more likely among schools with experienced faculty, when parents are seen as important partners in student skin cancer prevention, and when school principals and teachers have a lower personal risk phenotype.